UPAYA MENGUATKAN PROFIL PELAJAR PANCASILA MELALUI DESAIN PEMBELAJARAN SEJARAH BERBASIS KEBHINEKATUNGGALIKAAN - Danan Tricahyono (Universitas Negeri Malang, 2022)
The background of this article departs from the program of the Ministry of Education, Research, Technology, and Higher Education to establish the output of Indonesian education known as Pancasila students. The purpose of writing articles is to design a Bhinneka-based (diversity-based) historical learning. The writing of this article uses conceptual ideas. The student dimension of Pancasila has the characteristics of being the embodiment of lifelong Indonesian students who have global competence and behave following the values of Pancasila, with six main elements: faith, piety to God and noble character, global diversity, cooperation, independent, critical reasoning, and creative. The design of history learning based on a Bhinneka Tunggal Ika (unity in diversity) using the Kemp model is to identify problems and determine learning goals, establish and analyze the character of learners, analyze materials and various components related to learning tasks in conjunction with the achievement of learning goals, determine specific learning goals for learners, contain forms of systematic and logical delivery of materials, assess learning strategies, Determine methods as a means to convey materials, develop evaluation tools, choose learning resources that can support learning activities, and forms of learning activities. The learning material is about Hindu-Buddhist life by taking Ngadas society as a source of learning. The values of cooperation and respecting differences between fellow human beings can be a source of transparency for students to create a younger generation of Pancasilaists. The latter have intellectual advantages wrapped in a unique character.Latar belakang artikel ini berangkat dari program Kementerian Pendidikan, Riset, Teknologi, dan Pendidikan Tinggi untuk membentuk output pendidikan Indonesia yang dikenal dengan siswa Pancasila. Tujuan penulisan artikel adalah untuk merancang pembelajaran sejarah berbasis Bhinneka. Penulisan artikel ini menggunakan ide-ide konseptual. Dimensi peserta didik Pancasila memiliki ciri-ciri menjadi perwujudan peserta didik Indonesia sepanjang hayat yang memiliki kompetensi global dan berperilaku sesuai dengan nilai-nilai Pancasila, dengan enam unsur utama: iman, takwa kepada Tuhan YME dan akhlak mulia, keragaman global, kerjasama, mandiri, berpikir kritis, dan kreatif. Perancangan pembelajaran sejarah berbasis Bhinneka dengan menggunakan model Kemp adalah untuk mengidentifikasi masalah dan menentukan tujuan pembelajaran, menetapkan dan menganalisis karakter peserta didik, menganalisis materi dan berbagai komponen yang berkaitan dengan tugas pembelajaran dalam hubungannya dengan pencapaian tujuan pembelajaran, menentukan spesifik tujuan pembelajaran bagi peserta didik, memuat bentuk-bentuk penyampaian materi yang sistematis dan logis, menilai strategi pembelajaran, menentukan metode sebagai sarana untuk menyampaikan materi, mengembangkan alat evaluasi, memilih sumber belajar yang dapat mendukung kegiatan belajar, dan bentuk kegiatan pembelajaran. Materi pembelajaran tentang kehidupan Hindu-Budha dengan mengambil masyarakat Ngadas sebagai sumber belajar. Nilai-nilai kerjasama dan menghargai perbedaan antar sesama manusia dapat menjadi sumber transparansi bagi mahasiswa untuk menciptakan generasi muda Pancasilais. Yang terakhir memiliki keunggulan intelektual yang dibungkus dengan karakter yang unik.